Remote parent coaching in preschool mathematics: Evidence from Peru - Emma Näslund-Hadley; Juan Manuel Hernández-Agramonte; Carolina Méndez; Fernando Fernandez (Inter-American Development Bank (IDB), 2022)
We evaluate the effects of a 10-week intervention that randomly provided access to remote coaching to parents of preschool children over the summer break in Peru. In response to learning losses during school closures induced by COVID-19, education coaches offered guidance and encouragement to parents in activities designed to accelerate the development of core mathematical skills. We find that the intervention improved cognitive outcomes in mathematics by 0.12 standard deviations. Moreover, we show that remote coaches increase the likelihood and frequency of parental engagement in mathematics-related activities, suggesting that learning gains are driven by greater parental involvement in child skill development.
Keywords: :I20; I24; 330; Preschool learning; education technologies; interactive radioinstruction; parent engagement